Editorial - Md. Noon, Hazizan (International Islamic University Malaysia, 2019)
As one might be aware, the articles in the previous Issue were all country-specific which allowed the reader to gain deeper insights into the religious/civilisational issues that took place in the respective geo-political confines. Partly based on the same principle, we selected four main articles and one Viewpoint to form the contents of the current Issue. These are: “The Genesis and Evolution of the Modern Concept of Civilisation in Eighteenth and Nineteenth-Century Europe” by Mohd Helmi Mohd Sobri, “A Critique of Tadeusz Swietochowski’s Works on the Azerbaijan Democratic Republic (1918-1920) under the Prism of Edward Said’s Orientalism” by Elchin Shahinovich Huseynov and Tunku Mohar Tunku Mohd. Mokhtar, “The Role of Muslim Scholars in Kwara Politics up to the Fourth Republic” by Ibrahim Abdul Ganiyu Jawondo, “Malay Navigation And Maritime Trade: A Journey Through Anthropology and History” by Md. Salleh Yaapar and “The Chinese Civilisation Quest for The Great Harmony ( 大同 Da Tong) Through Humanness (仁 Ren)” [Viewpoint] by Peter Chang.....In the light of the above articles and viewpoint, it is pertinent to draw our attention to some highlights. Firstly, in the study of civilisation, or any other studies for that matter, we are fully aware of the coinage and popularisation of new terminologies from time to time....Terminologies that could stand the test of time would prevail and last longer. Such is the case for the term ‘civilisation’ which is still prevailing today. The term was found to also be debated along other terms like ‘civility’ and ‘culture’. In the Arab-Islamic context, the terms like ḥaḍārah, madaniyyah, tamaddun and thaqāfah also underwent such kind of intellectual scrutiny in the course of its journey to reach a more refined notion of civilisation….Secondly, in the context of development and civilisation, today’s reality is certainly not the same as in the past times. This applies to all aspects at both individual and societal levels....In each minute, there are numerous new things added to the already complex social entity making ‘cultural lag’ not only a reality of society but the gap that is created between one’s ability to embrace those new things and his old way of thinking becomes wider and hardly bridgeable. In such a situation, development may mean nothing to some people and this causes them to ask such question as: do we feel safer, better and happier with the advancement of knowledge and technologies?